Use of Neutrosophy in the Evaluation of a Health Education Program for Undergraduate Medical Students - Andrea Suárez López; María Isabel Fong Betancourt; Diana Lorena Jordán Fiallos (Neutrosophic Sets and Systems, 2022)
The study of problems that contribute to health education in university students is increasingly demanded by the scientific community, as it contributes to the prevention of diseases and thus encourages healthy lifestyles. In correspondence with the bibliographic review carried out in this research, it was found that this topic has been addressed by various scientific disciplines, but undoubtedly it is still required to deepen the link with Neutrosophy. Based on these arguments, the present research aims to apply Neutrosophy in the evaluation of a health education program for undergraduate medical students of the Regional Autonomous University of the Andes, in the Republic of Ecuador. During the development of this study, theoretical, empirical and statistical methods were taken into account, particularly descriptive neutrosophic statistics. The results obtained allow asserting that the program presented has a high level of relevance and can be applied in university educational practice.